The Potential Roles of Mucosa-Associated Invariant T Cells in the Pathogenesis of Gut Graft-Versus-Host Disease After Hematopoietic Stem Cell Transplantation - Gao, Meng-Ge; Hong, Yan; Zhao, Xiang-Yu; Pan, Xin-An; Sun, Yu-Qian; Kong, Jun; Wang, Zhi-Dong; Wang, Feng-Rong; Wang, Jing-Zhi; Yan, Chen-Hua; Wang, Yu; Huang, Xiao-Jun; et al. (Frontiers in Immunology, 2021)
Gut acute graft-versus-host disease (aGVHD) is a serious complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and is associated with high mortality. Mucosal-associated invariant T cells (MAITs) are a group of innate-like T cells enriched in the intestine that can be activated by riboflavin metabolites from various microorganisms. However, little is known about the function or mechanism of action of MAIT in the occurrence of gut aGVHD in humans. In our study, multiparameter flow cytometry (FCM) was used to evaluate the number of MAIT cells (MAITs) and functional cytokines. 16S V34 region amplicon sequencing analysis was used to analyse the intestinal flora of transplant patients. In vitro stimulation and coculture assays were used to study the activation and function of MAITs. The number and distribution of MAITs in intestinal tissues were analysed by immunofluorescence technology. Our study showed that the number and frequency of MAITs in infused grafts in gut aGVHD patients were lower than those in no-gut aGVHD patients. Recipients with a high number of MAITs in infused grafts had a higher abundance of intestinal flora in the early post-transplantation period (+14 days). At the onset of gut aGVHD, the number of MAITs decreased in peripheral blood, and the activation marker CD69, chemokine receptors CXCR3 and CXCR4 and transcription factors Rorγt and T-bet tended to increase. Furthermore, when gut aGVHD occurred, the proportion of MAIT17 was higher than that of MAIT1. The abundance of intestinal flora with non-riboflavin metabolic pathways tended to increase in gut aGVHD patients. MAITs secreted more granzyme B, TNF-α and IFN-γ under the IL-12/IL-18 stimulation (non-TCR signal) and secreted most of the IL-17 under the CD3/CD28 stimulation (TCR signal). MAITs inhibited the proliferation of CD4+ T cells in vitro. In conclusion, the lower number of MAITs in infused grafts was related to the higher incidence of gut aGVHD, and the number of MAITs in grafts may affect the composition of the intestinal flora of recipients early after transplantation. The flora of the riboflavin metabolism pathway activated MAITs and promoted the expression of intestinal protective factors to affect the occurrence of gut aGVHD in humans.